Patient satisfaction and associated factors in Addis Ababa’s public referral hospitals: insights from 2023 - Abebe, Dawit; Mesfin, Sinetibeb; Kenea, Luna Abebe; Alemayehu, Yosef; Andarge, Kostr; Aleme, Temsegen (Frontiers in Medicine, 2024)
Background: Currently, patient satisfaction is a major concern in the healthcare system of Ethiopia. Patient satisfaction with nursing care is considered an important factor in explaining patients' service quality. Satisfied patients are more likely to have a good relationship with nurses, which suggests improved quality of care.Objective: To assess the prevalence of patient satisfaction and its associated factors among admitted patients in Addis Ababa city public referral hospitals, Ethiopia 2023.An institutional-based cross-sectional study design was employed among 471 randomly selected patients from June 1 to July 30, 2023.Interviewer-administered a structured questionnaire was used to collect data. Patient satisfaction was measured by using the Newcastle Nursing Care Satisfaction Scale.Bivariable and multivariable logistic regressions were used to identify the factors associated with patient satisfaction.Result: 471 participants responded among 506 selected patients yielding a response rate of 93%. The satisfaction of patients was 47.8% (95% CI=42.9 %, 52.2%) Multiple logistic regression showed that participants aged 26-35 were less likely to be satisfied with nursing care [AOR = 0.25, 95% CI: 0.11, 0.56]. In contrast, those in the surgical ward [AOR = 3.85, 95% CI: 1.98, 7.45] and ophthalmology ward [AOR = 4.27, 95% CI: 1.81, 10.05] were more satisfied. No previous admission [AOR = 0.13, 95% CI: 0.07, 0.26],having no comorbidities [AOR = 13.4, 95% CI: 7.06, 25.4], and shorter admission duration [AOR = 9.14, 95% CI: 3.46, 24.11] were found to be factors with a significant association with patient nursing satisfaction Conclusions: Overall, just under one in every two admitted patients were satisfied, indicating areas for potential improvement in nursing care. Specific factors such as patients in the age range of 26 to 35 reported significantly lower levels of satisfaction, whereas patients in the surgical and ophthalmology wards, as well as those without comorbidities and with shorter hospital stays, reported significantly higher levels of satisfaction. These findings emphasize the importance of targeted strategies to enhance nursing care.